Applying nursing process : - Alfaro-LeFevre, Rosalinda (Lippincott, 2002)
This exciting revision of Applying Nursing Process - which received a Sigma Tau Best Pick Award - illustrates how to use the nursing process to think critically in today's fast-paced clinical practice. An emphasis on outcome-focused, evidence-based care guides the nurse on how to plan, provide, and evaluate care of the patient. Straight forward language, abundant examples, including valuable quote from nurses exemplifying current best practices, critical thinking exercises and case scenarios help the nurse think about independent and collaborative roles in various settings. This superb text explains how the nursing process has changed to a more dynamic, less linear approach, with a focus on proactivity to highlight the nurse' s role in the prediction, prevention, and management of health problems.